PELATIHAN PENGOLAHAN SAMPAH GELAS PLASTIK MENJADI TAS ETHNIK DI DESA BAMBAN - Fitria Khasanah; Lina Ferdiana; Reynaldi Arya Putera Kusuma; Risalatul Muawanah; Usna Vegaria (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2023)
One of the villages in the Malang district, East Java, namely Bamban Asrikaton Village, has a problem, namely the large amount of inorganic waste that has accumulated on the side of the road so that it interferes with the cleanliness and view of the environment. A group of youth organizations members are trying to minimize the accumulation of waste. The youth group collects and sorts waste to clean up the environment and then sells it at a fairly cheap price. Even though inorganic waste can be used to become objects that have a high selling value. Therefore, we provide training on processing plastic waste into bags. The implementation method consists of Observations related to conditions and problems in the Youth Organization group in Bamban Village, Licensing for the implementation of activities to the Head of the Hamlet and Head of the RT and Chair of the Youth Organization, Purchase of tools and materials used for training, Training for making Ethnic Bags, Training participants can follow the steps -steps exemplified by the PKM -PM Team in making Ethnic Bags, and preparing Activity reports. As an output form of the activity, namely increasing partners' knowledge about the dangers of waste, especially inorganic waste which is known to be very decomposed or takes a very long time to decompose as a whole, and increasing the creativity of Bamban Asrikaton villagers by providing knowledge about processing plastic drinking glass waste into a bag.